(untitled) (Stato, Chiese e pluralismo confessionale, 2024)
Tutela dei minori e prospettive di bilanciamento di diritti fondamentali ABSTRACT: The article analyses the complex issue of child protection in the context of ritual circumcision, identifying the fundamental rights to be balanced. In particular, the text focuses on the diverse landscape of regional health policies, which only in some cases provide coverage for non-therapeutic circumcision, with clear disparities between regions. SUMMARY: 1. Premise - 2. Circumcision and children’s rights - 3. Circumcision in public health - 4. Perspectives.